Phenomenological Explanation of Parent-Adolescent Conflict Among Girls Aged 16 to 17 Years - Niazi, Mohsen; Siadatian, Seyed Hossein; Majidi, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Adolescence is characterized as a developmental and challenging period marked by a wide range of changes in various psychological and physiological dimensions. One of the most significant issues reported by both adolescents and parents is the intensification of conflicts between them, which necessitates a deeper examination. Therefore, the aim of the present study was to provide a phenomenological explanation of the parent-adolescent conflict among girls aged 16 to 17 years. Methods and Materials: The data for this qualitative study were collected using the research tradition of lived experience and the method of semi-structured in-depth interviews through the process of coding (the 7-step Colaizzi method). The research population included 30 adolescent girls aged 16 to 17 years from the city of Kashan in 2023, who were analyzed using purposeful sampling and adherence to the principles of theoretical saturation. Findings: The results indicated the extraction of 7 main themes and 23 sub-themes. The main themes included: 1. Concerns about clothing and hijab, 2. Communication skills, 3. Value issues, 4. Academic challenges, 5. Preservation of dignity and individual respect, 6. Family-related factors, 7. Alignment with societal changes, which were examined in detail in the findings section. Conclusion: Utilizing the results of the present study facilitates the development of educational and therapeutic models to reduce conflict between adolescents and parents, and therapeutic interventions can also be performed on themes that were more frequently reported by adolescents.